(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay deals with a recent legislative proposal on the responsibility and punishability of insane offenders. After attempting to render intelligible the core of the proposal from the analysis of the heterogeneity of its theoretical matrix, we will highlight some problematic aspects that the proposal brings with it, and we will finally define its sense and value in the current political and epistemological struggle around psychiatric expertise through a comparison with a court case representative of the medico-legal state of our societies.